A The Impact of Tourism Regulations on Tourist Visit Performance: A Comparative Analysis of Indonesia and Singapore - Kuntariningsih, Apri; Andhi Supriyadi (An International Journal Tourism and Community Review, 2026)
Tourism regulations play a critical role in shaping destination competitiveness and influencing tourist travel decisions, yet empirical evidence on their effectiveness across different institutional contexts remains limited. This study investigates the impact of tourism regulations on tourist visit performance through a comparative quantitative analysis of Indonesia and Singapore. Using panel data covering the period 2010–2023, this research employs a fixed-effects regression model to examine the relationship between regulatory quality and tourist arrivals, while controlling for economic conditions and transport infrastructure. The findings reveal that tourism regulations have a positive and statistically significant effect on tourist visit performance in both countries. However, the magnitude of the effect is substantially stronger in Singapore, indicating higher regulatory efficiency and institutional effectiveness in translating policy interventions into tourism demand. These results support institutional and tourism demand theories, emphasizing that regulatory quality, rather than regulatory volume, is a key determinant of tourism performance. The study contributes to the tourism policy literature by providing cross-national empirical evidence on regulatory impacts and highlighting the importance of governance capacity in tourism development. From a policy perspective, the findings suggest that countries should prioritize regulatory coherence, administrative efficiency, and adaptive governance to enhance tourism competitiveness and resilience.